Performance and drug deposition of kappa-carrageenan microspheres encapsulating ciprofloxacin HCl: Effect of polymer concentration - Dewi Melani Hariyadi; Tutiek Purwanti; Dinda Maulydia; Cindy Alicia Estherline; Esti Hendradi; Mahardian Rahmadi (Wolters Kluwer Medknow Publications, 2021)
It has been known that in respiratory disease, antibiotic is selected for respiratory diseases or lung infections and this research focused on ciprofloxacin HCl as a model. The aim was to evaluate the effect of kappa-carrageenan polymer concentrations on characteristics, release, and drug deposition in the lung. Ciprofloxacin HCl-carrageenan microspheres were produced with kappa carrageenan (0.75%, 0.50%, and 0.25%) as polymer and KCl (1.5%) as crosslinker. Physical characteristics were included morphology, size, moisture content, swelling index, mucoadhesivity, drug loading, entrapment efficiency, and yield. Freeze-dried microspheres were inhaled by animal, and drug deposition was observed. Results showed that dried, smooth, and spherical microspheres of size of 1.34 to 1.70 μm and loading of 15.63% to 38.72%. Entrapment efficiency and yield were 25.38%-51.61% and 52.53%-63.19%, respectively. Mucoadhesivity was 0.0059-0.0096 kg force, and release in 24 h was 74.38%-81.02%. Release kinetics demonstrated Higuchi mechanism. Increasing carrageenan concentration affected size, loading, and efficiency but did not influence adhesivity, yield, and release. Higher amount of polymer caused the lower deposit on the lungs. Respirable size of ciprofloxacin HCl-kappa carrageenan microspheres was successfully achieved target site and prolonged residence time in lungs.